Non-Operative Rehabilitation Principles for Use in Individuals with Acetabular Dysplasia: A North American Based Delphi Study - Ashley E. Disantis; RobRoy L. Martin; Keelan Enseki; Victoria Spaid; Michael McClincy (International Journal of Sports Physical Therapy)
# Background